SUSTAINABLE PROFESSIONAL DEVELOPMENT OF COMPARATIVE STUDIES TEACHERS AT MAN IC TAPANULI SELATAN AND MAN IC PADANG PARIAMAN - Dalimunthe, Irwan Saleh; Hasibuan, Safriadi; Rangkuti, Ahmad Nizar (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The objectives of this research are (1) To find out the self-development of teachers in MAN IC Tapanuli Selatan and MAN IC Padang Pariaman; (2) To find out the scientific publications of teachers at MAN IC Tapanuli Selatan and MAN IC Padang Pariaman; (3) To find out the innovative work of teachers at MAN IC Tapanuli Selatan and MAN IC Padang Pariaman. (4) To find out the problems faced by teachers at MAN IC Tapanuli Selatan and MAN IC Padang Pariaman in participating in Sustainable Professional Development (PKB). This study uses a descriptive method, the data collection method is observation, documentation and interview, and the validity of the data in this study uses the extension of the research time, diligence of observation and triangulation by means of source triangulation. Data is analyzed by Data reduction which means summarizing, Presentation of data after data is reduced, and drawing conclusions. The results of the study show that (1) The self-development of teachers at MAN IC Tapanuli Selatan and MAN IC Padang Pariaman is carried out as functional diktat activities and Teacher Working Groups (KKG). (2) Scientific Publications of MAN IC Tapanuli Selatan and MAN IC Padang Pariaman Teachers, consisting of three activities, namely, achievements in scientific forums, scientific publications in the form of research results or scientific ideas in the field of formal education and publication of textbooks, enrichment books or teacher guidelines. Most teachers have already implemented it. (2) The Innovative Work of MAN IC Tapanuli Selatan and MAN IC Padang Pariaman Teachers has run smoothly and optimally. Innovative work carried out by teachers makes learning media in the classroom. (3) Problems that occur in MAN IC Tapanuli Selatan and MAN IC Padang Pariaman in participating in Teacher Sustainable Professional Development (PKB), which is related to learning where teachers still have minimal participation of a small number of teachers in participating in activities and in making journals by teachers.